2021
DOI: 10.1088/1755-1315/698/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Design and Feasibility Studies A Floating Photovoltaic to Supply Electricity for Isolated Island Village in Indonesia

Abstract: The Electricity power in Indonesia cannot covering of all Indonesia region especially on coastal isolated area. In this study, in order to overcome these problems this paper present the design of modular floating photovoltaic farm which could reach annual electricity house hold 1481 KWh. Floating photovoltaic farm must easy to install and deliver to isolated coastal village Indonesia, and modular floating farm necessary strength on the operation at Indonesian environment. Floating photovoltaic body was designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Mursid et al 15 developed a 3D model and carried out stress analyses of FPVs made from polyethylene (PE) and they also proposed the installation of such a system in Indonesia. 15 By means of the existing testbed, Lui et al 16 assembled one of the first sets of extensive, high-quality data about FPV operating conditions and system performance, including module temperatures on FPV systems, which are generally 5 C to 10 C lower than similar modules mounted on rooftop environments, and it has been found that those lower temperatures help increase energy yield. Overall, FPV systems tend to outperform PV systems set up on the ground or on rooftops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mursid et al 15 developed a 3D model and carried out stress analyses of FPVs made from polyethylene (PE) and they also proposed the installation of such a system in Indonesia. 15 By means of the existing testbed, Lui et al 16 assembled one of the first sets of extensive, high-quality data about FPV operating conditions and system performance, including module temperatures on FPV systems, which are generally 5 C to 10 C lower than similar modules mounted on rooftop environments, and it has been found that those lower temperatures help increase energy yield. Overall, FPV systems tend to outperform PV systems set up on the ground or on rooftops.…”
Section: Introductionmentioning
confidence: 99%
“…Given that situation, the development of FPV projects for such places is promising. Mursid et al 15 developed a 3D model and carried out stress analyses of FPVs made from polyethylene (PE) and they also proposed the installation of such a system in Indonesia 15 …”
Section: Introductionmentioning
confidence: 99%